Uric acid and cognitive decline: a double-edge sword?. Issue 2 (March 2018) - Latourte, Augustin; Bardin, Thomas; Richette, Pascal
Abstract : Purpose of review: This narrative review aims to highlight recent findings on the relation between uric acid level and cognitive decline or dementia. Recent findings: The antioxidant properties of uric acid, which have supported the hypothesis that uric acid may be neuroprotective, have been questioned by preclinical data. Studies investigating the relation between serum uric acid (SUA) level and Alzheimer disease are mostly cross-sectional, and results are often inconclusive. Similarly, data for an association between uric acid level and cognitive performance are inconsistent. There is some evidence that low SUA level might be associated with Parkinson disease, but studies are limited by methodological heterogeneity and risk of bias. Patients with gout may have decreased risk for Alzheimer disease, but the impact of treatment is unclear. Recent data suggest an increased risk of vascular dementia with high SUA level via increased cerebrovascular burden in older patients. The relation between SUA level and neurologic disorders may be U-shaped. Summary: We lack strong evidence for an association between low SUA level and cognitive decline over time. Conversely, high SUA level might increase the cerebrovascular burden and the risk of vascular dementia; physicians should continue to treat hyperuricemia when appropriate.